1998
DOI: 10.1001/jama.279.20.1615
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Acute Coronary Events With Lovastatin in Men and Women With Average Cholesterol Levels

Abstract: Context.-Although cholesterol-reducing treatment has been shown to reduce fatal and nonfatal coronary disease in patients with coronary heart disease (CHD), it is unknown whether benefit from the reduction of low-density lipoprotein cholesterol (LDL-C) in patients without CHD extends to individuals with average serum cholesterol levels, women, and older persons. Objective.-To compare lovastatin with placebo for prevention of the first acute major coronary event in men and women without clinically evident ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
2,463
10
113

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,763 publications
(2,634 citation statements)
references
References 17 publications
48
2,463
10
113
Order By: Relevance
“…Dyslipidemia, particularly elevated levels of low-density lipoprotein cholesterol (LDL-C), increases the risk of coronary artery disease (CAD) (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Dyslipidemia, particularly elevated levels of low-density lipoprotein cholesterol (LDL-C), increases the risk of coronary artery disease (CAD) (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…3 One randomized clinical drug trial lasting 5 years reported 12 breast carcinoma cases among pravastatin users and only 1 case in the placebo group (P ϭ 0.002), 4 but this finding was not confirmed in other clinical trials of statin use. [5][6][7] Evidence concerning the carcinogenicity of statins from clinical drug trials and observational studies remains inconclusive because of inconsistent results between studies, the limited range of statin exposure duration, and inadequate sample sizes. 4 -13 Contrary to concerns regarding the carcinogenicity of statins, a growing body of evidence suggests that statins may in fact have a chemopreventive potential against cancer.…”
mentioning
confidence: 99%
“…Several large-scale, randomized, placebo-controlled clinical trials have demonstrated that LDL cholesterol lowering with statin therapy reduces morbidity and mortality in patients with or at risk of cardiovascular diseases (7)(8)(9)(10). More recent active comparator statin trials have demonstrated that aggressive lowering of LDL cholesterol provides additional benefits over more moderate lowering.…”
Section: Cardiovascular Benefits Of Ldl Cholesterol Lowering With Stamentioning
confidence: 99%